THE SOLUTION FOR STUDY PROGRAMME LEARNING OUTCOME ALIGNMENT WITH STUDY COURSE LEARNING OUTCOME - Rollande, Raita; Mislevics, Antons (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The research question of this paper is - How can we better help professors with developing course descriptions and how we can help study program directors to reach study program aims through learning outcomes? This issue is very common for all Latvian higher education institutions as well as other higher education institutions outside of Latvia. It became clear after reading the new changes of the Law of Higher Education of the Republic of Latvia that two major changes had to be made first in course descriptions: updating the course descriptions to the new requirements and creating a mapping of the study programs. The decision was made to start work on a Course Management System. The goal purpose was to create a Course Management System that will help professors with developing course descriptions and will help study program directors to reach study program aims through learning outcomes. At first together with students the authors did a detailed analysis of the system and then developed it. Now the system is ready for implementation. Thanks to the developed system at Ventspils University of Applied Sciences has solved several important issues related to the course descriptions. For study programme learning outcome alignment with study course learning outcome will be used matrix method. CMS is web application what is developed using HTML, CSS, Javascript, and CSS frame Bootstrapare, PHP framework Laravel and MySQL.